HARPO: beam characterization of a TPC for gamma-ray polarimetry and high angular-resolution astronomy in the MeV-GeV range. (October 2015) - Wang, Shaobo; Bernard, Denis; Bruel, Philippe; Frotin, Mickael; Geerebaert, Yannick; Giebels, Berrie; Gros, Philippe; Horan, Deirdre; Louzir, Marc; Poilleux, Patrick; Semeniouk, Igor; Attié, David; et al.
Abstract: A time projection chamber (TPC) can be used to measure the polarization of gamma rays with excellent angular precision and sensitivity in the MeV-GeV energy range through the conversion of photons to e + e − pairs. The Hermetic ARgon POlarimeter (HARPO) prototype was built to demonstrate this concept. It was recently tested in the polarized photon beam at the NewSUBARU facility in Japan. We present this data-taking run, which demonstrated the excellent performance of the HARPO TPC.